High IKKα expression is associated with reduced time to recurrence and cancer specific survival in oestrogen receptor (ER)‐positive breast cancer. Issue 7 (6th January 2017) - Bennett, Lindsay; Quinn, Jean; McCall, Pamela; Mallon, Elizabeth A.; Horgan, Paul G.; McMillan, Donald C.; Paul, Andrew; Edwards, Joanne
Abstract : The aim of our study was to examine the relationship between tumour IKKα expression and breast cancer recurrence and survival. Immunohistochemistry was employed in a discovery and a validation tissue microarray to assess the association of tumour IKKα expression and clinico‐pathological characteristics. After siRNA‐mediated silencing of IKKα, cell viability and apoptosis were assessed in MCF7 and MDA‐MB‐231 breast cancer cells. In both the discovery and validation cohorts, associations observed between IKKα and clinical outcome measures were potentiated in oestrogen receptor (ER) positive Luminal A tumours. In the discovery cohort, cytoplasmic IKKα was associated with disease‐free survival ( p  = 0.029) and recurrence‐free survival on tamoxifen ( p  < 0.001) in Luminal A tumours. Nuclear IKKα and a combination of cytoplasmic and nuclear IKKα (total tumour cell IKKα) were associated with cancer‐specific survival ( p  = 0.012 and p  = 0.007, respectively) and recurrence‐free survival on tamoxifen ( p  = 0.013 and p  < 0.001, respectively) in Luminal A tumours. In the validation cohort, cytoplasmic IKKα was associated with cancer‐specific survival ( p  = 0.023), disease‐free survival ( p  = 0.002) and recurrence‐free survival on tamoxifen ( p  = 0.009) in Luminal A tumours. Parallel experiment with breast cancer cells in vitro demonstrated the non‐canonical NF‐κB pathway was inducible by exposure to lymphotoxin in ER‐positive MCF7 cells and not in ER‐negative MDA‐MB‐231 cells. Reduction in IKKα expression by siRNA transfection increased levels of apoptosis and reduced cell viability in MCF7 but not in MDA‐MB‐231 cells. IKKα is an important determinant of poor outcome in patients with ER‐positive invasive ductal breast cancer and thus may represent a potential therapeutic target. Abstract : What's new? The dysregulation of signaling pathways involving members of the nuclear factor kappa B (NF‐κB) family is a significant feature in breast cancer. Of particular consequence is aberrant activation of the noncanonical NF‐κB pathway, which is associated with activity of the inhibitor of NF‐κB kinase α (IKKα). In our study, increased IKKα levels were associated with reduced cancer‐specific survival and reduced recurrence‐free survival in oestrogen receptor (ER‐)‐positive breast cancer patients treated with tamoxifen. In ER‐positive breast tumour cells, IKKα silencing triggered apoptosis and decreased cell viability. According to the findings, IKKα is a possible target in endocrine‐treated breast cancer.